Culture and user-interface design for older users in Malaysia - Hisham, Syariffanor; Edwards, Alistair D. N. (ISG, 2007)
The implications of age-related changes in perceptual, cognitive and psycho-motor abilities for older users’ computer interaction are well-documented. Although studies in Age Associated Memory Impairment (AAMI) show that semantic memory is unaffected by ageing, many researches in the area of computing and older users only emphasize working memory capabilities. Cultural norms and knowledge learned from living in a specific environment tend to remain as people get older. Culture norms also have a significant impact on users’ acceptance and performance with computer technology. To demonstrate such impact, this paper reviews listening and speaking modes using a Malaysian scenario.